Sexually transmitted infections and infectiousness beliefs among people living with HIV/AIDS: implications for HIV treatment as prevention. - Kalichman, S C; Eaton, L; Cherry, C (HIV medicine, 2010)
Sexually transmitted infections (STIs) significantly impact the health of people living with HIV/AIDS, increasing HIV infectiousness and therefore transmissibility. The current study examined STIs in a community sample of 490 HIV-positive men and women.
Keywords: Adolescent; Condoms; Female; Georgia; Health Knowledge, Attitudes, Practice; HIV Infections; Humans; Incidence; Male; Multivariate Analysis; Qualitative Research; Risk Factors; Risk-Taking; Sexual Behavior; Sexually Transmitted Diseases; Substance-Related Disorders; Viral Load; Young Adult